A prospective observational study of trial of labor after cesarean in rural India. Issue 2 (May 2015) - Soni, Anjali; Sharma, Chanderdeep; Verma, Suresh; Justa, Usha; Soni, Pawan K.; Verma, Ashok
Abstract Objective To determine the success rate of trial of labor after cesarean (TOLAC) in rural India. Methods The present prospective observational study enrolled pregnant women attending Dr Rajendra Prasad Government Medical College, Kangra, India, in 2013. Eligible women had a previous low-segment cesarean delivery and had a singleton pregnancy with cephalic presentation. Women in labor were managed as per the institutional protocol. Results In total, 482 women were included. TOLAC led to a vaginal delivery in 383 (79.6%) women. Overall, 2 (0.4%) women had scar rupture, and 4 (0.8%) had scar dehiscence. Fetal death was recorded in one woman with scar rupture, for whom peripartum hysterectomy was necessary. Blood loss was significantly lower among the 316 women with normal vaginal delivery than among the 99 who underwent cesarean (P < 0.001). Blood transfusion was required in 2 (0.6%) women with normal vaginal delivery and 2 (2.0%) with cesarean delivery (P = 0.05). The proportion of neonates who had to be admitted to intensive care did not differ significantly by mode of delivery (P = 0.06). Conclusion Under strict supervision, TOLAC is a reasonable option even in rural India.